The benefit of context for facial-composite construction. Issue 4 (9th November 2015) - Skelton, Faye C.; Frowd, Charlie D.; Speers, Kathryn E
Abstract : Purpose: – The purpose of this paper is to investigate whether the presence of a whole-face context during facial composite production facilitates construction of facial composite images. Design/methodology/approach: – In Experiment 1, constructors viewed a celebrity face and then developed a facial composite using PRO-fit software in one of two conditions: either the full-face was visible while facial features were selected, or only the feature currently being selected. The composites were named by different participants. The authors then replicated the study using a more forensically valid procedure: in Experiment 2 non-football fans viewed an image of a premiership footballer and 24 hours later constructed a composite of the face with a trained software operator. The resulting composites were named by football fans. Findings: – In both studies, the presence of the facial context promoted more identifiable facial composites. Research limitations/implications: – Current composite software was deployed in a conventional and unconventional way to demonstrate the importance of facial context. Practical implications: – Results confirm that composite software should have the whole-face context visible to witnesses throughout construction. Although some software systems do this, there remain others that present features in isolation and these findings show that these systems are unlikely to be optimal. Originality/value: – This is the first study to demonstrate the importance of a full-face context for the construction of facial composite images. Results are valuable to police forces and developers of composite software.